Analysis of Students’ Mathematical Reasoning Ability on Junior High School - Usman, Ulfiani; Juniati, Dwi; Khabibah, Siti (IKIP Siliwangi, 2026)
Students’ mathematical reasoning ability (MRA) is an essential component of mathematics learning, particularly for solving non-routine problems. However, many junior high school students still rely on procedural strategies without sufficient conceptual understanding, resulting in weak reasoning skills, especially in geometry topics such as the Pythagorean Theorem, indicating the need for a detailed analysis of students’ mathematical reasoning ability. This study aims to analyze junior high school students’ mathematical reasoning ability on the Pythagorean Theorem based on four indicators: proposing conjectures, performing mathematical transformations, providing logical justification, and drawing conclusions. A descriptive qualitative approach was employed involving 31 eighth-grade students of SMP Negeri 1 Raha selected through purposive sampling. Data were collected using an open-ended mathematical reasoning ability test related to the Pythagorean Theorem and supported by semi-structured interviews. Data analysis was conducted using Miles and Huberman’s interactive model, consisting of data reduction, data display, and conclusion drawing and verification. The results indicate that 6% of students demonstrated high mathematical reasoning ability, 8% were categorized as moderate, and 86% were classified as low. Most students experienced difficulties in formulating conjectures, transforming contextual problems into mathematical models, providing logical justification, and drawing valid conclusions. In conclusion, students’ mathematical reasoning ability on the Pythagorean Theorem remains relatively low. Therefore, instructional strategies that emphasize conceptual understanding, reasoning processes, justification, and reflective thinking are necessary to improve students’ mathematical reasoning abilities.